KARAKTERISTIK CAMPURAN ASPAL PANAS (ASPHALT CONCRETE-BINDER COURSE) MENGGUNAKAN ASPAL POLIMER - Bambang Edison (Universitas Pasir Pengaraian, 2010)
Nearly 99% of Indonesia's flexible pavement made of bituminous mixtures. Damage to the pavement road in general is cracking and permanent deformation. Therefore, the use of additive (additive) on the hot asphalt mix is one way to resolve the issue. One of the ingredients that can improve the quality of pavement is to use materials with a polymer modified bitumen (asphalt modifier).This study aimed to analyze the characteristics of Marshall from the use of asphalt with the addition of polymer additives Starbit E-55 brands in the mix (AC-BC) through the Marshall with the durability testing modifications.